Repressing organized crime in Italy: recent developments and shortcomings in substantive criminal law - Panebianco, Giuseppina (Zeitschrift für die gesamte Strafrechtswissenschaft, 2017)
The expression “organized crime” cannot be found in the Italian Criminal Code (CC), whereas it appears in the Code of Criminal Procedure (CCP)2 and in other laws (e.g. Law no. 354/1975 on the Penitentiary System). The Italian Criminal Code provides for the crime of associazione per delinquere (an association formed to commit crimes)3. More specifically, Italian criminal law provides for a general model fact situation in article 416 CC which shares some similarities with article 129 of the German Criminal Code